Wallace & Gromit : the complete cracking collection [videorecording (Blu-Ray)]. (Shout! Factory, 2023)
The complete collection of four cracking half-hour specials and ten short films featuring the charming and eccentric inventor Wallace, and his faithful, four-legged friend Gromit!